Antropologia cultural e política em Rousseau: o estatuto anti-etnocêntrico na Carta a d’Alembert sobre os espetáculos - SILVA, Irlene Veruska Batista da (2023)
The aim of the present dissertation is to investigate Jean-Jacques Rousseau's (1712- 1778) critique of French ethnocentrism based on the work Letter to M. d'Alembert on Spectacles (1758) – henceforth Letter. The Letter was born in response to an entry called Geneva written in the Encyclopedia by the philosopher Jean le Rond d'Alembert (1717-1783). In Geneva, d'Alembert extolled the qualities of theatre and suggested opening a company of comedians in the city of the same name. In terms of methodological perspective, we propose to look at Rousseau's work from the interpretation of Claude Lévi-Strauss (1908-2009), as well as from the teachings offered by Pierre Bourdieu (1930-2002). We think that the levistraussian perspective – initiated in the text Jean-Jacques Rousseau, Founder of the Sciences of Man (1962) – helps us to reflect on the hypothetical possibility of an anti-ethnocentric status in the work of the Genevan. Through the lens of Bourdieu (2007), his concepts – symbolic capital, trajectory – allow the observation of the insertion of the citizen of Geneva in the fields (music, philosophy, inter alia) from the positions he takes in the concrete disputes facing “abstract” issues (Moral, Inequality, among others). One of the main results that our research allows us to point out is that in the Letter the verification of the diversity of peoples should print and correspond to a multiplicity of spectacles; the particularity of each people clashes with the Enlightenment perspective of universalization of a model of man and civilization – notably, Europeans; and represents an intellectual break with the philosophes of the Enlightenment, specifically with Denis Diderot (1713-1784) and François-Marie Arouet, known as Voltaire (1694- 1778).